2017
DOI: 10.1007/s12519-017-0031-8
|View full text |Cite
|
Sign up to set email alerts
|

Etiology and clinical features of viral bronchiolitis in infancy

Abstract: For the time being, the diagnosis of bronchiolitis remains clinical. The isolation of the responsible respiratory pathogens does not seem to confer to the prognosis of the disease severity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
27
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 73 publications
4
27
0
4
Order By: Relevance
“…The predominance pattern of respiratory viruses in bronchiolitis reported in this study is consistent with that reported by several previous narrative reviews [71][72][73]. Regardless of https://doi.org/10.1371/journal.pone.0242302.g001…”
Section: Discussionsupporting
confidence: 92%
“…The predominance pattern of respiratory viruses in bronchiolitis reported in this study is consistent with that reported by several previous narrative reviews [71][72][73]. Regardless of https://doi.org/10.1371/journal.pone.0242302.g001…”
Section: Discussionsupporting
confidence: 92%
“…23 24 Subsequently, low-grade fever, wheezing, crepitations on auscultation and signs of increased respiratory effort develop, such as nasal flaring, chest wall retraction and tachypnoea. 23 In very young infants under 6 weeks of age, apnoea associated with RSV infection is an important indication for hospital admission. 25 In most children, however, reduced oral intake and hydration status are the main indications for admission.…”
Section: Clinical Diagnosis Childrenmentioning
confidence: 99%
“…However, there is not yet any reported definite distinction between the severity of the disease and the type of viruses. So, to report the different clinical experiences can further contribute to composing a standardized definition of severity of RTIs, as Fretzayas and Moustaki suggested (12).…”
Section: Discussionmentioning
confidence: 99%